Rebuilding Communities through Waqf: Restoring Ethical Values and Social Cohesion in Contemporary Muslim Societies - Isma’il Iliyasu Danladi; Adamu Abubakar Muhammad; Yusuf Isa Sawaba; Murjanatu Yusuf; Maryam Babani Muhammad (IDRIS Darulfunun Institute, 2026)
In the context of present-day challenges in the Muslim world such as erosion of social cohesion, growing moral decay, loss of public confidence, family disruption, disengagement among youth, and widening socio-economic disparities, while much attention has been focused on waqf as an institution to fight poverty, expand education, promote healthcare, and economic empowerment, relatively little work has been done on its function as a civilizational vehicle to reinstate morality and rekindle social bonds. This article, therefore, puts forward an argument for viewing the waqf not as just a pious endowment but as a resilient institutional form that can serve to restore the ethical values and rebuild social solidarity in Muslim communities. Through an extensive library research of classical literature on Islamic history of waqf, and its contemporary research on Maqasid al-Shariah, social capital, community building, etc, this study establishes that waqf has throughout Islamic history been utilized to enhance education, strengthen families, build trust among the general public, reinforce a sense of citizenship, preserve the environment, strengthen collective identity, etc, beyond mere economic well-being. The article then outlines a Value-Centred Waqf Framework to position waqf as a multi-dimensional tool for reinculcating values, rekindling social ties, enhancing public service, and contributing to sustainable development of Muslim communities. Ultimately, this article concludes that a regeneration of waqf by its higher objectives in the Shariah provides a viable practical approach for strengthening Muslim communities from the bottom-up so they can better navigate the social challenges they face in the current global era.